A review of epidemiology of fall among elderly in India - Alex Joseph; Dhasarathi Kumar; M Bagavandas (Wolters Kluwer Medknow Publications, 2019)
Background: Injuries have become a major public health concern. Recent data show that globally over 5 million people lose their life due to injury every year. Especially in low- and middle-income countries, people living below the poverty line are drastically scathed due to injuries. Objective: The objective of this paper is to find the magnitude and risk factors of fall among the elderly in India. Materials and Methods: A systematic search was done by using Google Scholar and PubMed. Results: The selected studies revealed that the prevalence of fall ranges from 26% to 37% across various regions, fall injuries are associated with poor vision, vertigo, imbalance, fear of falling, history of fall, presence of osteoarthritis, visual impairment, hearing impairment, and depression. This study has shown the risk of fall was higher among female elderly population. Conclusion: The major contributing factors for fall injuries are aging, visual impairment, previous history of fall, depression, and gait problem. Females have a higher risk of fall comparatively to males.